Spatiotemporal changes of optical signals in the somatosensory cortex of neuropathic rats after electroacupuncture stimulation. Issue 1 (December 2017) - Cha, Myeounghoon; Chae, Younbyoung; Bai, Sun; Lee, Bae
Abstract Background Peripheral nerve injury causes physiological changes in primary afferent neurons. Neuropathic pain associated with peripheral nerve injuries may reflect changes in the excitability of the nervous system, including the spinothalamic tract. Current alternative medical research indicates that acupuncture stimulation has analgesic effects in various pain symptoms. However, activation changes in the somatosensory cortex of the brain by acupuncture stimulation remain poorly understood. The present study was conducted to monitor the changes in cortical excitability, using optical imaging with voltage-sensitive dye (VSD) in neuropathic rats after electroacupuncture (EA) stimulation. Methods Male Sprague–Dawley rats were divided into three groups: control (intact), sham injury, and neuropathic pain rats. Under pentobarbital anesthesia, rats were subjected to nerve injury with tight ligation and incision of the tibial and sural nerves in the left hind paw. For optical imaging, the rats were re-anesthetized with urethane, and followed by craniotomy. The exposed primary somatosensory cortex (S1) was stained with VSD for one hour. Optical signals were recorded from the S1 cortex, before and after EA stimulation on Zusanli (ST36) and Yinlingquan (SP9). Results After peripheral stimulation, control and sham injury rats did not show significant signal changes in the S1 cortex. However, inflamed and amplified neural activities were observed in the S1 cortex of nerve-injured rats. Furthermore, the optical signals and region of activation in the S1 cortex were reduced substantially after EA stimulation, and recovered in a time-dependent manner. The peak fluorescence intensity was significantly reduced until 90 min after EA stimulation (Pre-EA: 0.25 ± 0.04 and Post-EA 0 min: 0.01 ± 0.01), and maximum activated area was also significantly attenuated until 60 min after EA stimulation (Pre-EA: 37.2 ± 1.79 and Post-EA 0 min: 0.01 ± 0.10). Conclusion Our results indicate that EA stimulation has inhibitory effects on excitatory neuronal signaling in the S1 cortex, caused by noxious stimulation in neuropathic pain. These findings suggest that EA stimulation warrants further study as a potential adjuvant modulation of neuropathic pain.